Deliberative process in sharing information with different audiences: Eye-tracking correlates. Issue 4 (April 2022) - Martín-Luengo, Beatriz; Myachykov, Andriy; Shtyrov, Yury
Research on conversational pragmatics demonstrates how interlocutors tailor the information they share depending on the audience. Previous research showed that, in informal contexts, speakers often provide several alternative answers, whereas in formal contexts, they tend to give only a single answer; however, the psychological underpinnings of these effects remain obscure. To investigate this answer selection process, we measured participants' eye movements in different experimentally modelled social contexts. Participants answered general knowledge questions by providing responses with either single (one) or plural (three) alternatives. Then, a formal (job interview) or informal (conversation with friends) context was presented and participants decided either to report or withdraw their responses after considering the given social context. Growth curve analysis on the eye movements indicates that the selected response option attracted more eye movements. There was a discrepancy between the answer selection likelihood and the proportion of fixations to the corresponding option—but only in the formal context. These findings support a more elaborate decision-making processes in formal contexts. They also suggest that eye movements do not necessarily accompany the options considered in the decision-making processes.